Educational association with zoonotic related knowledge and practices of livestock farmers in selective districts of Nepal - Bagale, Kosh Bilash; Adhikari, Ramesh; Acharya, Devaraj (Journal of Health Promotion, 2022)
This study aims to assess the educational association with knowledge and preventive practices of livestock farmers toward the common zoonoses. A descriptive cross- sectional quantitative research design was followed in the study. The total sample size was 380 livestock farmers from randomly selected three districts of Nepal. Systematic sampling technique was applied for data collection. The data were calculated using descriptive statistics. Univariate, bivariate, and multivariate analyses were performed. The majority of the respondents (52.4%) had basic level education. Similarly, more than two-thirds (67.6%) adopted agro-farming and less than one in ten (7.9%) had livestock as a major occupation in their households. In this study bird flu (95.8%) and rabies (90.7%) are highly known zoonoses and swine flu is average (54.2%) in terms of respondents’ knowledge. The finding shows that a large number of respondents with higher education had good knowledge about zoonoses and followed better zoonoses preventive practices. Among the higher educated respondents; practice to avoid sick animal consumption was 86.7 percent, practice to children avoiding livestock contact was 45.5 percent, pregnant women avoiding livestock exposure was 49 percent and pre-exposure vaccination practices was 55.8 percent which showed significant statistical association with their level of education. However, a significant number of respondents with higher education still were unaware about many common zoonoses and poor preventive practices. Therefore; education should be accessible in every community whereas; health education with specific zoonoses in the school curriculum and zoonoses related training for livestock farmers should be warranted.